Do you really want to visit a coral reef? - Heos, Bridget; Fabbri, Daniele, 1978- (Mankato, MN : Amicus Illustrated, 2015)
"A child goes on a deep-sea diving adventure in the Great Barrier Reef in Australia, learning about the ocean, and encountering animals and plants that make their homes in this biome. Includes world map of coral reefs and glossary"--Provided by publisher.
Includes bibliographical references (p. 24).
Booklist, October 2014.
Booklist.
2.6
K-3
Keywords: Coral reef ecology -- Juvenile literature; Coral reefs and islands -- Juvenile literature; Coral reef ecology; Coral reefs and islands; Coral reef ecology; Coral reefs and islands; Coral reef ecology; Coral reefs and islands; Picture books for children